Aviation Workforce Optimization: Examining the Interdependence of Operational Discipline, Job Satisfaction, and Professional Competence - Agus Supriyadi; Nidya Dudija; Dian Indiyati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This research investigates the influence of operational discipline, job satisfaction, and professional competence on employee performance within the aviation sector, focusing specifically on Airport Operational Support Services. A quantitative causal-explanatory method was employed, using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) technique. The sampling process applied a stratified random method, involving 338 participants from different job levels. The findings reveal that both operational discipline and professional competence have a significant and positive impact on employee performance. Conversely, job satisfaction was found to have a negative effect. Theoretically, this study deepens the understanding of the interplay between these variables within high-risk work environments. On a practical level, it offers strategic insights for improving performance through targeted initiatives in discipline and competency enhancement. The study also provides a valuable contribution to the formulation of more comprehensive and contextually appropriate human resource management strategies in the airport support services industry.